Macrophage activity in tumour development - Eljaszewicz, Andrzej; Gackowska, Lidia; Kubiszewska, Izabela; Jankowski, Michał; Urbańska, Milena; Wiese, Małgorzata; Helmin-Basa, Anna; Michałkiewicz, Jacek; Zegarski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2010)
Macrophages are derived from peripheral blood monocytes. Due to their pleiotropic biological activities they have been ascribed both a progressive (M1 phenotype) and regressive (M2 phenotype) impact on tumour growth. Anti- or pro-tumoural functions of macrophages are the consequence of their pro- and anti-inflammatory properties. The polarization in the direction of the described activities is connected with the activating agent. The macrophages within the tumour are referred to as tumour-associated macrophages (TAMs). Upon activation by cancer cells they mostly exhibit M2 phenotype and are able to release numbers of cytokines, chemokines, enzymes and inflammatory mediators. TAMs can enhance tumour growth and metastasis. Increasing TAMs infiltration correlates with cancer growth and poor prognosis in a variety of human carcinomas.